Advances of Proteomics in Novel PTM Discovery: Applications in Cancer Therapy. Issue 5 (28th February 2019) - Wang, Yang; Zhang, Jing; Li, Bin; He, Qing‐Yu
Abstract: Protein posttranslational modification (PTM) is a critical mechanism to enhance the diversity of protein species and functions in organisms. Currently, many different PTMs are discovered and found to be involved in a wide range of cellular processes. The aberrant regulation of PTM dynamics is reported to contribute to cancer development. Phosphorylation and acetylation are the best studied PTMs, and the application of high‐resolution mass spectrometry‐based proteomics and specific antibody‐based enrichment technologies significantly promotes novel PTM discovery. This review discusses methods for global PTM identification, including antibody‐based enrichment and chemical probe‐based identification. Several acylations, such as propionylation, butyrylation, succinylation, malonylation, and crotonylation, are recently found to influence both histone and nonhistone proteins and to be intimately linked with the progression of cancer. It is proposed that targeting novel PTM dynamics by pharmacological inhibitors has great potential for cancer therapy. Abstract : This review summarizes the current progress and proteomic strategies in posttranslational modification (PTM) identification, focusing on the application of high‐resolution mass spectrometry‐ and specific antibody‐based enrichment technologies on novel PTM discovery. Several acylations are found to link with cancer development. Their dynamic regulators and relevant inhibitors are discussed, suggesting that targeting novel PTM dynamics has great potential for cancer therapy.